Evaluating the Real-World Representativeness of Participants with Mild Cognitive Impairment in Canadian Research Protocols: a Comparison of the Characteristics of a Memory Clinic Patients and Research Samples - Huang, Vivian (Can Geriatr J, 2020)
BACKGROUND: Studies of mild cognitive impairment (MCI) employ rigorous eligibility criteria, resulting in sampling that may not be representative of the broader clinical population. OBJECTIVE: To compare the characteristics of MCI patients in a Calgary memory clinic to those of MCI participants in published Canadian studies. METHODS: Clinic participants included 555 MCI patients from the PROspective Registry of Persons with Memory SyMPToms (PROMPT) registry in Calgary. Research participants included 4,981 individuals with MCI pooled from a systematic literature review of 112 original, English-language peer-reviewed Canadian studies. Both samples were compared on baseline sociodemographic variables, medical and psychiatric comorbidities, and cognitive performance for MCI due to Alzheimer’s disease and Parkinson’s disease. RESULTS: Overall, clinic patients tended to be younger, more often male, and more educated than research participants. Psychiatric disorders, traumatic brain injury, and sensory impairment were commonplace in PROMPT (up to 83% affected) but > 80% studies in the systematic review excluded these conditions. PROMPT patients also performed worse on global cognition measures than did research participants. CONCLUSION: Stringent eligibility criteria in Canadian research studies excluded a considerable subset of MCI patients with comorbid medical or psychiatric conditions. This exclusion may contribute to differences in cognitive performance and outcomes compared to real-world clinical samples.